Analisis Pengaruh Pengeluaran Pemerintah Sektor Pendidikan, Kesehatan, Korupsi, dan Pertumbuhan Ekonomi terhadap Indeks Pembangunan Manusia di Negara APEC - Dita Ayu Anantika; Hadi Sasana (Universitas Diponegoro, 2020)
Human development is a global issue that is experienced in almost every country. The problem of human development becomes a matter that must be resolved in a sustainable manner because the low quality of human capital can be an obstacle to the economic growth of society in achieving prosperity. The purpose of this study is to examine the effect of education sector government expenditure, health sector government expenditure, corruption, and economic growth on the human development index. This research uses secondary data covering 20 APEC member countries in the 2012-2017 period. The method used is panel data regression with the Fixed Effect model (FEM). The results of this study indicate that government expenditure in the health sector and corruption has a positive and significant effect on the human development index. While government spending in the education sector and economic growth has a negative and significant effect on the human development index.